Math and science software [technology 1999 analysis and forecast]. - Kornbluh, K. (IEEE spectrum)
During the next five years, the huge change taking place in the computing environment due to the Internet will give math and scientific software a buffeting as bruising as the transition from DOS to Windows or from workstations to desktop computers. But in the near future, the Year 2000 bug will probably be on the minds of many engineers and scientists, who will attempt to make sure that their work will not be affected by it. Besides that, software capabilities will expand while prices shrink, making many powerful programs more affordable. Such high-end applications as solids modeling, for example, are becoming less costly, thanks to an increase in the processing speed of PCs. In addition to changing the nature of computing, the Internet is changing the way math and scientific software works and has become a way to distribute software, in some cases free of charge. Also worth noting is the renaissance of Fortran, which through some powerful programs has extended its use as a data analysis and visualization tool. And voice input is emerging as a useful means of entering data in computer-aided design (CAD) programs